Presentation and physical therapy management using a neuroplasticity approach for patients with hypermobility-related upper cervical instability: a brief report - Chalela, Susan; Russek, Leslie N. (Frontiers in Neurology, 2024)
BackgroundUpper cervical instability (UCI) is a potentially disabling complication of the connective tissue disorders hypermobile Ehlers-Danlos Syndrome and Hypermobility Spectrum Disorders (hEDS/HSD). UCI can impact various neurological structures, including the brainstem, spinal cord, cranial nerves, and blood supply to and from the brain, resulting in complex neurological signs and symptoms in this population. The current study was an observational study applying recent expert consensus recommendations for physical therapy assessment and management of patients with UCI associated with hEDS/HSD.MethodsThis was a retrospective observational study describing how the clinical decision-making model was used to screen, examine, and treat three patients with highly irritable hEDS/HSD-related UCI, resulting in complex neurological presentation. The treatment used a neuroplasticity approach, including proprioception and motor control training emphasizing patient education and biofeedback. Outcome measures tracked progress.ResultsAll patients started with significant disability associated with UCI. One patient returned to full function with intermittent flares that he was able to manage. The second patient continued to have mild-moderate irritability but returned to parenting responsibilities and full-time work. The third patient required cervical fusion and remained disabled but was better able to minimize flares. The number of initial red and yellow flags was associated with the final outcomes, suggesting that the decision-making model might be useful for predicting patient prognosis.ConclusionThis brief report applies recent recommendations for safely evaluating and managing hypermobility-related UCI and provides a first step in experimental studies to test both the assessment and physical therapy treatment approaches.